Almost η-conformal Ricci solitons in (LCS)_3-manifolds - Siddiqi, Mohd Danish; Chaubey, Sudhakar K. (Sarajevo Journal of Mathematics, 2022)
The aim of the present paper is to study the properties of three dimensional Lorentzian concircular structure manifolds ((LCS)_3-manifolds) endowed with almost η-conformal Ricci solitons. Also, we discuss the η-conformal gradient shrinking Ricci solitons on (LCS)_3-manifolds. Finally, the examples of almost η-conformal Ricci soliton on an (LCS)_3-manifold are provided in the region where (LCS)_3-manifold is expanding.